Intermediate English as a Foreign Language learners’ formulaic language speaking proficiency: Where does the teaching of lexical chunks figure? - Albelihi, Hani Hamad M. (Frontiers in Psychology, 2022)
Corporate social responsibility (CSR) plays an important role in education institutions. This research aims to investigate the impact of learning lexical chunks on the EFL Saudi learners’ (aged 13 to 17) speaking fluency and study examines how CSR improves quality. The study uses an intervention with intermediate Saudi learners comprising lexical chunks based upon the books Collocation in Use and Common Idioms in English. Findings obtained from the post-test show that the experimental groups scored significantly better when compared to their performance in the pre-test of speaking fluency. On the contrary, the difference in the performance of the control group between the pre and post-tests is not significant as far as speaking fluency is concerned. The findings also show that the experimental group participants had favorable sentiments regarding explicit lexical chunk training. The research has theoretical and practical consequences in teaching and learning a foreign/second language.